Mechanical Technology Prototype Innovation of Computer Numerical Control from Electric Apparel as A Medium for Education - Laka, Oktafatahna; Sudariyanto, Sudariyanto; Dapa, Anju Pritia (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
E-waste is a waste in the form of electronic devices that are not used anymore. One example is the personal computer components (PCs) that have been damaged or already left as an old technology that it can be no longer used. So far, e-waste PCs have not been widely used or recycled for more useful purposes, so its existence tends to be a waste that has the potential to cause pollution. Based on these conditions, it is necessary to do a research for e-waste PC can be processed and reused, one of which can be used as machine prototype computer numerical control (CNC) with three axis which can then be used as a medium for studies. This research begins by designing the physical form of a 3 axis CNC machine with the software Autodesk Inventor device. Then, it was made a prototype machine that part of its components taken from the former PC unused components. As a driving force, the prototype CNC machine used stepper motor combined with Arduino UNO Microcontroller based control system. This machine is then operated with a PC using Universal G-Code Sender and GRBL (Coding Gate) based CNC programming system. With a working area of 42 mm x 42 mm and a 17 mm depth of feed, the prototype CNC machine can eventually be used as a study medium for schools that do not have CNC machines due to their high cost and high maintenance costs.